Histological Characteristics of Vanaraja, Aseel and Kadaknath Meat : 10.5958/2581-6616.2020.00021.3 - Singh, V. P.; Pathak, V.; Gangwar, Neeraj K.; Gupta, S. K. (Journal of Meat Science, 2020)
Present study was conducted to assess the histological characteristics of Vanraja, Aseel and Kadaknath meat. The muscle fibre thickness of breast and thigh muscles were separately assessed and found highest in Vanraja and lowest in Kadaknath meat. Muscle bundle thickness was also found lowest in Kadaknath meat while no definite pattern was indicated in Vanraja and Aseel. It was evident from the histological characteristics that the breast and thigh muscles showing highest muscle fibre thickness were lowest in permysium diameter and vice versa. The muscle fibre and endomysium thickness both were lowest in Kadanath. The collagen, reticular and elastic fibres indicated the toughness in muscles and found highest in Vanraja breed. On comparison of breast and thigh muscles, thigh muscles showed comparatively more number of collagen, reticular and elastic fibres.